Perancangan Sistem Informasi Tata Tertib Sekolah Berbasis Digital pada SMAN 18 Kabupaten Tangerang - Haikal Muzakii; Afiani Agus Abdillah; Fery Zepanya Sinaga; Moch. Irfan Afriyana (CV. Shofanah Media Berkah, 2026)
Driven by advancements in information technology, academic institutions are urged to enhance their data management workflows, including the supervision of student conduct. SMAN 18 Kabupaten Tangerang currently handles violation tracking, point allocation, and disciplinary reporting through manual procedures. Consequently, the school encounters operational bottlenecks, such as delayed updates, potential data misplacement, and sub-optimal student monitoring. Addressing this issue, this research aims to design a Digital School Discipline Information System based on the Waterfall method. The sequential nature of the Waterfall model ensures a structured development process, spanning from initial requirements analysis to final system maintenance. The system is engineered using PHP, with MySQL serving as the primary database management system. Key features deployed include student record keeping, infraction and achievement logging, point tracking, comprehensive reporting, and an automated notification system for students. The outcome of this study indicates that the newly developed platform successfully delivers faster, more accurate, and highly efficient data processing. Additionally, it empowers homeroom and counseling teachers to track student discipline through a centralized, digital ecosystem.